Impaired Recent Verbal Memory in Pornography-Addicted Juvenile Subjects - Pukovisa Prawiroharjo; Hainah Ellydar; Peter Pratama; Rizki Edmi Edison; Sitti Evangeline Imelda Suaidy; Nya’ Zata Amani; Diavitri Carissima (Neurology Research International)
We aimed to find the differences in memory capabilities between pornography-addicted and nonaddicted juveniles. We enrolled 30 juveniles (12–16 y) consisting of 15 pornography addiction and 15 nonaddiction subjects. We used Rey Auditory Verbal Learning Test (RAVLT) to measure verbal memory, Rey–Osterrieth Complex Figure Test (ROCFT) for visual memory, along with Trail Making Test A and B (TMT-A and TMT-B) for attention. We found a significant reduction in the RAVLT A6 result of the addiction group (nonaddiction vs addiction: 13.47 ± 2.00 vs 11.67 ± 2.44, MD = −1.80, p=0.04), but not in ROCFT or attention tests. Analysis in sex subgroups yielded no sex-specific difference. We concluded that pornography addiction may be associated with impaired recent verbal memory in juveniles, regardless of sex and without association to attention.